2001
DOI: 10.1038/35094573
|View full text |Cite
|
Sign up to set email alerts
|

A neurocognitive perspective on language: The declarative/procedural model

Abstract: What are the psychological, computational and neural underpinnings of language? Are these neurocognitive correlates dedicated to language? Do different parts of language depend on distinct neurocognitive systems? Here I address these and other issues that are crucial for our understanding of two fundamental language capacities: the memorization of words in the mental lexicon, and the rule-governed combination of words by the mental grammar. According to the declarative/procedural model, the mental lexicon depe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

54
647
9
21

Year Published

2003
2003
2015
2015

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 790 publications
(731 citation statements)
references
References 90 publications
(103 reference statements)
54
647
9
21
Order By: Relevance
“…This suggests that regular and irregular past tense forms may both be stored, given that retrieving both forms is problematic but recognizing them is not. Fourth, whereas in normally developing children and adults, frequency effects for regular inflected forms are absent, inconsistent or weak (Pinker, 1999;Ullman, 2001aUllman, , 2001c, they are consistently demonstrated in children and adults with SLI, both in past-tense production (Oetting and Horohov, 1997;Ullman and Gopnik, 1994;Ullman and Gopnik, 1999;van der Lely and Ullman, 2001) and in plural production . Fifth, van der Lely and Christian (2000) found that children with SLI produced compounds with regular as well as irregular plurals inside them (e.g., rats-eater and mice-eater).…”
Section: Phonology Children and Adults With Sli Also Exhibit Impairmmentioning
confidence: 99%
See 4 more Smart Citations
“…This suggests that regular and irregular past tense forms may both be stored, given that retrieving both forms is problematic but recognizing them is not. Fourth, whereas in normally developing children and adults, frequency effects for regular inflected forms are absent, inconsistent or weak (Pinker, 1999;Ullman, 2001aUllman, , 2001c, they are consistently demonstrated in children and adults with SLI, both in past-tense production (Oetting and Horohov, 1997;Ullman and Gopnik, 1994;Ullman and Gopnik, 1999;van der Lely and Ullman, 2001) and in plural production . Fifth, van der Lely and Christian (2000) found that children with SLI produced compounds with regular as well as irregular plurals inside them (e.g., rats-eater and mice-eater).…”
Section: Phonology Children and Adults With Sli Also Exhibit Impairmmentioning
confidence: 99%
“…Specifically, it has been posited that important aspects of the difference between these two types of mappings can be captured by the distinction between procedural memory and declarative memory, another well-studied memory system (Ullman, 2001a(Ullman, , 2001cUllman et al, 1997). According to this view -referred to as the Declarative/Procedural (DP) model -idiosyncratic mappings are stored in a memorized "mental lexicon" that depends on declarative memory, whereas the learning and use of rule-governed computations involves a "mental grammar" that depends on procedural memory.…”
Section: Languagementioning
confidence: 99%
See 3 more Smart Citations